Team Approach: The Management of Adolescents and Adults with Scoliosis and Spina Bifida. Issue 3 (1st March 2022) - Bradko, Viachaslau; Castillo, Heidi; Conklin, Michael; Fremion, Ellen; Rocque, Brandon; Hanson, Darrell; Sanz-Cortes, Magdalena; Whitehead, William; Castillo, Jonathan
Abstract : » Globally, the prevalence of myelomeningocele, the most common subtype of spina bifida, is 0.2 to 6.5 per 1, 000 live births. In the U.S., adults account for >67% of the overall population with spina bifida. » With an estimated prevalence of up to 50%, scoliosis is one of the most common and severe orthopaedic conditions in patients with myelomeningocele. » The variable effects that scoliosis can have on an individual, the comorbidities associated with progressive scoliosis, and the risks associated with spine surgery call for a strong partnership and care coordination between medical and surgical teams to deliver a patient-centered approach. » A coordinated, structured, planned, and incremental team approach can help individuals achieve the overall goals of functionality and independence, as well as successful transition to adulthood. » Teams should consider a patient's social determinants of health (e.g., poverty or language barriers) and the effect of scoliosis on quality of life before proceeding with spinal deformity correction.